Using a Heuristic-Systematic Model to assess the Twitter user profile's impact on disaster tweet credibility. (October 2020) - Son, Jaebong; Lee, Jintae; Oh, Onook; Lee, Hyung Koo; Woo, Jiyoung
Highlights: The profile information of Twitter users can be used as informational cues that reflect tweets' source credibility. The number of followers as a reputation credibility cue increases the probability of quick retweeting. The affiliation length of a Twitter account as a cue for social presence increases the probability of quick retweeting. The number of recent tweets as a recency credibility cue increases the probability of quick retweeting. Abstract: Journalists, emergency responders, and the general public use Twitter during disasters as an effective means to disseminate emergency information. However, there is a growing concern about the credibility of disaster tweets. This concern negatively influences Twitter users' decisions about whether to retweet information, which can delay the dissemination of accurate—and sometimes essential—communications during a crisis. Although verifying information credibility is often a time-consuming task requiring considerable cognitive effort, researchers have yet to explore how people manage this task while using Twitter during disaster situations. To address this, we adopt the Heuristic-Systematic Model of information processing to understand how Twitter users make retweet decisions by categorizing tweet content as systematically processed information and a Twitter user's profile as heuristically processed information. We then empirically examine tweet content and Twitter user profiles, as well as how they interact to verify the credibility of tweets collected during two disaster events: the 2011 Queensland floods, and the 2013 Colorado floods. Our empirical results suggest that using a Twitter profile as source-credibility information makes it easier for Twitter users to assess the credibility of disaster tweets. Our study also reveals that the Twitter user profile is a reliable source of credibility information and enhances our understanding of timely communication on Twitter during disasters.